One-dimensional array of gold nanoparticles fabricated using biotemplate and its application to fine FET. (11th May 2018) - Ban, Takahiko; Uenuma, Mutsunori; Migita, Shinji; Okamoto, Naofumi; Ishikawa, Yasuaki; Uraoka, Yukiharu; Yamashita, Ichiro; Yamamoto, Shin-ichi
Abstract: By synthesizing AuS nanoparticles (NPs) with spherical shell protein (ferritin) and using a V-groove, a one-dimensional array of NPs was formed at the bottom of the V-groove. It has been reported that AuS NPs are converted to Au NPs by UV/ozone treatment. Floating gate memory (FGM) was fabricated by applying this one-dimensional array to V-grooved junctionless (JL) FETs, V-grooved nin-like-type FETs, and pip-like-type FETs, which are fine FETs. In JL-FETs, it is considered that conversion occurred because of good charge storage efficiency, and operation in the opposite direction to normal FGM operation was seen. In the nin-like and pip-like types devices, the same operation as in conventional FGM was shown, and the width of the memory window was about the same size as when one electron entered one NP. The one-dimensional arrangement of the metal NPs used in this study is considered to be applicable to various fields of nanotechnology.